Моделювання ущільнення конічної порошкової заготовки в закритій жорсткій матриці - Хоменко, О. І.; Баглюк, Г. А. (НТУ "ХПІ", 2014)
Розглянуто математичну модель однобічного ущільнення конічної заготовки двома пуансонами в закритій жорсткій матриці в припущенні наявності радіальної складової плину матеріалу у циліндричних (технологічних) частинах матриці. Описано методику комп'ютерного моделювання процесу при ущільненні окремо верхнім та нижнім пуансонами. З'ясовано, що комп'ютерне моделювання у порівнянні з натурним призводить до якісно подібної картини розподілу пористості. Деякі кількісні відхилення можна пояснити як припущеннями при моделюванні, так i похибками експерименту.

Conic powder billets are of exceptional interest both practical to produce high-density powder details and theoretical to provide appropriate computing models predicting details properties.Computer simulation of conic powder billet compaction in the closed rigid die was realised basing on the direct variation method combined with the elements of visioplastic method. Strain rate tensor components are obtained using material flow equations then energy functional is formed using these components and minimized to obtain unknown parameters. Then these parameters are used to obtain new position of some fixed points at the billet section to calculate deformation and local porosity changes. Qualitative similarity of porosity distribution for computated model and real laminated billet was found. Some quantitative differences make necessary model assumptions futher check.
Simulation of conic powder billet compaction in the closed rigid die
Keywords: комп'ютерне моделювання; розподіл пористості; порошкові матеріали; ущільнення; матриця; пуансони; computer simulation; powder material; compaction; die; puncheon